Role of intraperitoneal onlay mesh in actuality for hernia - González Gómez, Santiago; Guzmán-Brito, Karla Paola; Méndez Pérez, Alan Amado; Kaloyan Lopez, Salvador Zadur; Gómez Vela, Carlos Miguel (International Surgery Journal, 2025)
This review evaluates the current evidence and outcomes associated with minimally invasive ventral and incisional hernia repairs, focusing on the use of intraperitoneal onlay mesh (IPOM). Long-term data indicate that IPOM is effective and safe in appropriately selected patients, with low recurrence and complication rates comparable to other surgical techniques. Advances in minimally invasive approaches, including minimum incisional laparoscopic Only surgery (MILOS), extended totally extraperitoneal (eTEP), and robotic-assisted repairs, have demonstrated benefits such as reduced postoperative pain, fewer wound complications, and shorter hospital stays compared to traditional open methods. The choice of surgical technique and mesh placement should be individualized, considering patient factors, hernia characteristics, and available technology to optimize outcomes. Emerging evidence supports the growing role of minimally invasive hernia repair as a standard approach in modern surgical practice.